Injuries among World Cup ski and snowboard athletes - Floerenes, T. W.; Nordsletten, L.; Heir, S.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2012)
There is little information available on injuries to World Cup skiers and snowboarders. The aim of this study was to describe and compare the injury risk to World Cup athletes in alpine skiing, freestyle skiing, snowboarding, ski jumping, Nordic combined and cross country skiing. We performed retrospective interviews with the International Ski Federation (FIS) World Cup athletes from selected nations during the 2006-2007 and 2007-2008 winter seasons and recorded all acute injuries occurring during the seasons. We interviewed 2121 athletes and recorded 705 injuries. There were 520 (72%) time-loss injuries and 196 (28%) severe injuries (absence >28 days). In freestyle skiing, alpine skiing and snowboarding, there were 27.6, 29.8 and 37.8 time-loss and 14.4, 11.3 and 13.8 severe injuries per 100 athletes per season, respectively. In Nordic combined, ski jumping and cross country skiing, there were 15.8, 13.6 and 6.3 time-loss and 3.3, 5.6 and 0.7 severe injuries per 100 athletes per season, respectively. In conclusion about 1/3 of the World Cup alpine, freestyle and snowboard athletes sustain a time-loss injury each season, while the risk is low in the Nordic disciplines. A particular concern was the high proportion of severe injuries observed among alpine, freestyle and snowboard athletes, which is in contrast to most other sports.